SOCIAL JUSTICE AND MANAGEMENT OF HIGHER EDUCATION - ABDULLAHI, Nimota Jibola kadir (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2024)
AbstractA significant issue related to social justice in higher education is the lack of equitable access to quality education for all individuals regardless of their socio-economic background. This problem is rooted in issues such as rising tuition costs, limited financial aid options, disparities in resources and opportunities among different communities, and systematic barriers that prevent marginalized groups from pursuing higher education. The purpose of this study was to investigate the relationship between social justice and the management of higher education. The research used a survey instrument and a quantitative research design. Statistical techniques including SPSS version 20.0, and SMART PLS software were used to analyze the received questionnaire and test the hypotheses. Social justice represented three distinct factors, i.e., affordable education, safe and inclusive environment, and language accessibility; management of higher education was indicated by three dimensions, governance structure, quality assurance as well and student service. The result also demonstrated the validity and reliability of each factor. The findings show a positive and strong relationship between affordable education, a safe and inclusive environment, language accessibility, and management of higher education. The study recommends that the government should make education more affordable, necessary, free, accessible, acceptable, and flexible enough to adjust to societal changes. Also, should provide a safe and inclusive environment as well as multilateral interaction to ensure language accessibility. The study's conclusions show that affordable education, a safe and inclusive environment, language accessibility, and management of higher education have a good and significant association.